Anti‐Toxoplasma activity and chemical compositions of aquatic extract of Mentha pulegium L. and Rubus idaeus L.: An in vitro study. Issue 7 (8th June 2020) - Mohammad Rahimi, Hanieh; Khosravi, Mojdeh; Hesari, Zahra; Sharifdini, Meysam; Mirjalali, Hamed; Zali, Mohammad Reza
Abstract: This study aimed to determine the chemical compositions of crude aquatic extracts of M. pulegium L. and R. idaeus L., and their anti‐ Toxoplasma activity. Crude aquatic extraction of aerial parts of R. idaeus L. and M. pulegium L. was performed. GC‐MS and HTPLC analyses were carried out. MTT assay was performed on Vero cells treated by different concentrations (Log −10 from 10 −1 to 10 −6 ) of the extracts. The anti‐ Toxoplasma activity of the concentrations was investigated using vital staining. Menthol (99.23%) and limonene (0.227%) were the major compounds of the aquatic extract of M. pulegium L. Phytochemical compositions of R. idaeus L. were terpenoids, esterols, and flavonoids. The cell toxicity of M. pulegium L. was lower than R. idaeus L. (CC50 > 10 −2 versus. ≥ 10 −4 ). Aquatic extract of M. pulegium L. showed higher anti‐ Toxoplasma activity (LC50 ≥ 10 −6 ) than R. idaeus L. (LC50 ≥ 10 −5 ). Statistically significant cell toxicity and anti‐ Toxoplasma activity ( p  < .05) were seen regarding the different concentrations of R. idaeus L. and M. pulegium L. Both R. idaeus L. and M. pulegium L. revealed anti‐ Toxoplasma activities. Cell toxicity of R. idaeus L. was significantly higher than M. pulegium L. M. pulegium L. extract could be more applicable due to its lower cell toxicity. Abstract : In the current study, we determined chemical compositions of M. pulegium L. and R. idaeus L. extracts and evaluated their effects on acute toxoplasmosis that the results were promising.